Evaluating the Efficacy of Chemical and Herbal Endodontic Irrigants in Smear Layer Removal: An In-vitro Analysis - Kanika Singh Dhull; Nayana Shriram Anasane; Sumit Singh; D. R. Mahesh; Vinay Rao; Meena Jain (Journal of Pharmacy and Bioallied Sciences)
Aim: The current research is designed to analyze the smear layer (SL) removal efficacy of different endodontic irrigants via scanning electron microscope (SEM). Materials and Methods: Eighty extracted premolars were gathered and allocated into four groups (n = 20) based on the array of endodontic irrigants employed: Group 1: Normal saline (NS), Group 2: 17% EDTA (Ethylenediaminetetraacetic acid), Group 3: Neem leaf extract (NLE), and Group 4: Garlic solution (GS). SL elimination was evaluated beneath SEM at upper, intermediate, and apical levels of root canals. Results: The acquired data was evaluated using the non-parametric equivalent test. Groups 2 and 3 had the most effective SL clearance performance, followed by Group 4, while Group 1 had the lowest effectiveness at the upper, intermediate, and apical levels. An intergroup comparison revealed that Group 3 had successful SL reduction at the apical level. Conclusion: Group 3 outperformed the other groups in eliminating the SL at the upper, intermediate, and apical thirds.